Pediatric benign transient hyperphosphatasemia: Clinical course and inflammatory ratios - Tolga Kasap; Samet Can Tekin; Hakan Sarbay; Korhan Yavuz (Turkish Journal of Pediatric Disease, 2026)
Objective: Benign transient hyperphosphatasemia (BTH) is a self-limited condition characterized by marked isolated serum alkaline phosphatase (ALP) elevation in children without evidence of bone or hepatobiliary disease. This study aimed to describe the clinical course of pediatric BTH and to test the hypothesis that Neutrophil-to-lymphocyte ratio (NLR) and platelet-to-lymphocyte ratio (PLR) differ between children with BTH and healthy controls. Materials and Methods: In this single-center retrospective study, we screened all pediatric ALP measurements (0–18 years) recorded between 2018 and 2025. Children were included if ALP was at least 2 times the age-specific upper reference limit, liver-related biochemical parameters were normal, there was no clinical evidence of bone or hepatobiliary disease, and ALP normalized during follow-up. NLR and PLR were compared with those of age and gender similar healthy controls without known chronic disease, medication use, or evidence of recent or ongoing infection or inflammatory conditions. Results: Thirty-nine children met the inclusion criteria, with a mean age of 51.9±59.7 months (range, 3–166 months). Of these, 69.2% were younger than 3 years and 59.0% were female. Mean ALP at presentation was 1006.2±1061.9 U/L (range 504–6576). ALP normalized spontaneously within 8.5±3.9 week (range 3–17). Compared with controls, the BTH group had significantly lower NLR (0.85 vs 2.66; p